LGG-36. DESMOPLASTIC INFANTILE GANGLIOGLIOMA (DIG) WITH A PPP1CB-ALK FUSION IN A 6-YEAR-OLD GIRL. (4th December 2020) - McDonald, William; Nagib, Mahmoud; Jenkins, Robert; Ida, Cristiane; Halling, Kevin; Skrypek, Mary; Bendel, Anne
Abstract: Desmoplastic infantile astrocytoma (DIA) and desmoplastic infantile ganglioglioma (DIG) are benign glioneuronal tumors that typically occur in infants, involve the superficial cerebral cortex, and have an excellent prognosis. DIA/DIG are a distinct molecular entity based on DNA methylation profiling. BRAF600 mutations are frequently reported in DIG/DIA. A recent comprehensive genetic analysis of infantile hemispheric gliomas identified 2 unique groups: group 1 harbored alterations in the receptor tyrosine kinase (RTK) genes ALK, ROS1, NTRK, and MET and group 2 harbored alterations in the RAS/MAPK pathway. We report a case of a 6.5-year-old girl who presented with seizures and right homonymous hemianopia. MRI of her brain demonstrated a large cystic/solid left hemispheric mass with remodelling of the overlying skull, consistent with a long-standing process. She underwent a gross total resection (GTR) and pathology demonstrated a DIG with a PPP1CB-ALK gene fusion (exon 5 to exon 20) identified by RNA sequencing. She remains disease free 12 months following GTR. A literature review identified 4 reported cases of pediatric brain tumors with PPP1CB-ALK gene fusions including: a 3-month-old with a hemispheric high-grade glioma which recurred 4 years later and pathology showed mature ganglioglioma, with both tumors showing the identical PPP1CB-ALK gene fusion; a 10-month-old infant with a hemispheric low-grade glioma; an infant with a "congenital" hemispheric high-grade glioma; and a child with an astrocytoma with no further clinical data. PPP1CB-ALK gene fusion appears to be a rare oncogenic driver in gliomas of infancy, including DIG.